The Situation and the Opportunistic Executive - Bryan, Stanley E. (Academy of Management Journal, 1962)
Examines the attitude of corporate executives and ways in which managers behave opportunistically in responding to business situations. Discussion on corporate decision-making; Details of leadership; Relationship of executives with their subordinates; Assessment of power structure and social status.